Determinants of Work-from-Home Productivity among Higher Education Institution Employees during the Covid-19 Pandemic in Malaysia - Zahir Osman,; Zulaihan Ismail ,; Bibi Nabi Ahmad Khan,; Noral Hidayah Alwi, (ASEAN Journal of Open and Distance Learning, 2020)
This study focuses on evaluating direct relationships between workplace environment, peer support, employee motivation and organisational support, and employee productivity support within higher education institutions in Malaysia during the Covid-19 pandemic. The Structural Equation Model technique was utilised to assess the direct effects of workplace environment at home, peer support, employee motivation, and organisational support on employee productivity. The model was designed and later analysed using the Partial Least Square procedure on data collected from a survey that yielded 579 usable questionnaires. The results demonstrated that workplace environment, peer support, and employee motivation have a positive and significant influence on employee productivity, while organisational support has a negative and significant influence on employee productivity. The findings suggest that higher education institutions should give greater emphasis on strengthening the workplace environment at home, peer support, employee motivation, and organisational support to ensure employee productivity is high if a work-from-home policy is implemented. (Abstract by authors)